Biogas Production Optimization from Palm Oil Mill Effluent: Experiments with Anaerobic Reactor - Mussen Lamoh, Malcolm; Jackson Joy, Eugene; Rashid, Mamunur; Islam, Shahidul; Hashmi, Saleem (International Journal of Integrated Engineering, 2020)
The research domain of this work is the implementation of waste-to-energy [WtE] strategy for achieving sustainability in renewable energy supply and environment. This paper aims to present a research conducted on biogas production performance of anaerobic digestion process of palm oil mill effluent (POME). This research attempts to address the problem relating to poor biogas production performance of anaerobic digester experienced by industries with POME. Various published papers have suggested that the performance of the currently available continuous stirred-tank reactor (CSTR) based anaerobic reactor is significantly poor and not technically and financially feasible to use. A two-stage CSTR has been used with carbon-to-nitrogen (C/N) enriched inoculum at different pH for the POME digestion. The anaerobic reactor was operated at temperature 35 â„ƒ with various range of inputs. The Design Expert software is used to determine the range and levels of inputs and to determine the number of experimental runs with different combinations of inputs factors. The findings of this research demonstrate that the optimum biogas production was achieved at significant (p-value<0.05) level of organic materials utilization (R2=62.26%) in digestion process at organic loading rate (OLR) of 5 g.VSS/L.d, C/N of 30.5, and pH of 6.6. This study concludes that the biogas production performance of CSTR could be improved by using optimum level of C/N and OLR based POME substrate. The findings of this research would be useful in palm oil mills for optimizing biogas production from POME as WtE. The novelty of this research is the use of C/N enriched inoculum (11<C/N<40) prepared from banana peel in the POME substrate for producing biogas.